Accessibility through universal design approach: public buildings in Putrajaya / Syazwani Abdul Kadir - Abdul Kadir, Syazwani (2014)
This research aimed to evaluate the accessibility of several public buildings in Putrajaya through a more universal approach, based on buildings’ compliance and persons with disabilities’ (PWD) feedbacks. Research objectives were to evaluate compliance of public facilities provided in case study buildings to Malaysia Standards for accessibility and Universal Design principles, and to identify PWD level of satisfaction for public facilities and their perception on the overall accessibility of case study buildings. This research incorporated mixed methodology of two categories of access audit; site observation and interview with PWD participants. Site observation measured compliance of public facilities with standards design guidelines, while interview assessed the buildings’ accessibility through close-ended questionnaires and open-ended interviews with four participants (visually impaired person, hearing impaired person, wheelchair-bound person, and crutches user). Five public buildings of different functions were chosen as the case studies; Department of Immigration building, Natural History Museum, Perdana Leadership Foundation building, Putrajaya International Convention Centre, and Tuanku Mizan Mosque. Findings showed that in terms of accessibility compliance, there are some areas for improvement especially in the provision of accessibility for sensory impaired users. In terms of participants’ feedbacks, their satisfaction and perception on the accessibility of case study buildings vary based on their type of impairment. However, there are two main issues that were similarly emphasized by them; emergency means of escape and staff assistance. The research concluded that a universal approach in creating barrier-free environment and conducting access audit is efficient in solving multifaceted accessibility issues in the built environment.